An asymmetric porous Ti tube, a preparation method and application thereof

CN118341978BActive Publication Date: 2026-10-13SICHUAN SIDANENG ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410445301.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-15
Publication Date
2026-10-13
Estimated Expiration
2044-04-15

AI Technical Summary

Technical Problem

但由于沉积材料的粉末粒度和支撑层的粉末粒度相差大,在相同的烧结工艺下,烧结程度不一致,使得支撑层和分离层之间的收缩率相差大,导致分离层开裂、破损、结合强度低等问题

Benefits of technology

[0025](1)本发明得到的多孔钛管包括内部的大孔支撑层和设置在其外壁的细孔分离层,多孔非对称钛管兼具大通量和高过滤精度;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118341978B_ABST
    Figure CN118341978B_ABST
Patent Text Reader

Abstract

The application discloses an asymmetric porous Ti tube, a preparation method and application, and comprises the following steps: step 1: ball milling TiH2 powder and a space-occupying agent respectively; mixing the ball-milled TiH2 powder and the space-occupying agent in a solvent to obtain a mixed solution; adding the mixed solution into a dispersant pre-prepared liquid to fully mix to obtain a slurry; wherein the mass ratio of the TiH2 powder and the space-occupying agent in the slurry is 3.5-9:1; step 2: coating the slurry obtained in step 1 on the surface of a porous Ti support layer to obtain a green body; step 3: drying and sintering the green body obtained in step 2 to obtain the required asymmetric porous Ti tube; the porous Ti tube obtained by the application comprises an inner macroporous support layer and a microporous separation layer arranged on the outer wall of the macroporous support layer, and the asymmetric porous Ti tube has both high flux and high filtration precision.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of metal porous material preparation technology, specifically to an asymmetric porous Ti tube, its preparation method, and its application. Background Technology

[0002] Porous metallic materials combine the advantages of both structural and porous materials, exhibiting characteristics such as low density, high specific strength, large specific surface area, high temperature resistance, corrosion resistance, sound insulation, heat insulation, and high permeability. They have been developed into a novel type of structural functional material, demonstrating broad application prospects in numerous fields including aerospace, chemical engineering, building materials, metallurgy, petrochemicals, machinery, medicine, and environmental protection. With the rapid development of industry, more typical application scenarios and usage requirements are constantly emerging, leading to significant advancements in the materials, preparation methods, and structural design of porous materials. Benefiting from their inherent unique properties, porous metallic materials are attracting increasing attention, becoming an important component of materials science, and continuously evolving towards high performance, long lifespan, and low cost.

[0003] In recent years, the demand for high-precision, high-efficiency sintered metal porous materials has been increasing in industries such as petrochemicals, power, and energy. Clearly, the pore structure of traditional porous materials presents a significant contradiction between high filtration accuracy and low flow rate. The air and water filtration resistance of porous materials is mainly related to factors such as pore size, thickness, and tortuosity factor. Pore size directly affects filtration accuracy, while the tortuosity factor is often determined by the preparation method. Therefore, the goal of high flow rate and high accuracy can only be achieved by controlling the pore size and reducing the thickness of the porous material. Asymmetric porous materials, where pore size and porosity are inconsistent along the thickness direction, are mainly composed of macropores, while the thickness of the fine pore layer for controlling accuracy is extremely low. They mainly consist of two structures: one is composed of a macroporous matrix support layer and a fine pore separation layer; the other is a gradient porous material, where the pore size and porosity vary gradient along the thickness direction.

[0004] Currently, the main method for preparing asymmetric porous materials is to deposit a layer of fine powder onto a macroporous substrate through methods such as spraying, dip coating, scraping, or centrifugal sedimentation, followed by sintering. However, due to the large difference in particle size between the deposited material and the supporting layer, the degree of sintering is inconsistent under the same sintering process. This results in a large difference in shrinkage rates between the supporting layer and the separation layer, leading to problems such as cracking, damage, and low bonding strength in the separation layer. In particular, in pure metal porous materials without a concentration gradient, the coating layer is difficult to bond with the supporting layer during secondary sintering, making it difficult to obtain a complete asymmetric porous material. Summary of the Invention

[0005] This invention addresses the problems existing in the prior art by providing an asymmetric porous Ti tube, its preparation method, and its application.

[0006] The technical solution adopted in this invention is: a method for preparing an asymmetric porous Ti tube, comprising the following steps:

[0007] Step 1: Ball mill the TiH2 powder and the spacer separately; disperse the ball-milled TiH2 powder and spacer in a solvent and mix to obtain a mixed solution; add the mixed solution to the dispersant pre-prepared liquid and mix thoroughly to obtain a slurry; wherein the mass ratio of TiH2 powder to spacer in the slurry is 3.5 to 9:1;

[0008] Step 2: Coat the slurry obtained in Step 1 onto the surface of the porous Ti support layer to obtain a green body;

[0009] Step 3: After drying the green blank obtained in Step 2, sinter it to obtain the desired asymmetric porous Ti tube.

[0010] Furthermore, the sintering in step 3 is gradient sintering, and the sintering regime is as follows:

[0011] Low-temperature sintering:

[0012] Stage 1: Heat to 120-150℃ and hold for 20-40 minutes;

[0013] In stage 2, when the temperature is below 300℃, the temperature is increased at a rate of ≤5℃ / min; when the temperature is above 300℃, the temperature is increased at a rate of less than 3℃ / min to reach 300-600℃, and then the temperature is maintained at a gradient for 3-8 hours.

[0014] Medium-temperature sintering: Heat to 750-850℃ and hold for 1-5 hours;

[0015] High-temperature sintering: Heat to 850-1000℃ and hold for 0.5-2 hours.

[0016] Furthermore, the placer in step 1 is K2SO4; the dispersant pre-liquid in step 1 is composed of polyvinyl butyral and solvent mixed at a mass ratio of 0.5 to 2:1; wherein the mass ratio of the total amount of dispersant pre-liquid, placer, and TiH2 powder to solvent in the slurry is 5 to 8: 7 to 10: 5 to 8; the particle size of the TiH2 powder is 500 to 100 mesh, and the ball milling process of the TiH2 powder is as follows: ball-to-material ratio of 3 to 5:1, ball milling time of 3 to 18 hours; the ball milling process of the placer is as follows: ball-to-material ratio of 3 to 6:1, ball milling time of 20 to 60 hours.

[0017] Furthermore, stage 2 of the sintering process is a gradient sintering process, which is divided into at least two steps.

[0018] Furthermore, the porous Ti support layer in step 2 is formed by pressing and sintering Ti powder, wherein the particle size of the Ti powder is 500-100 mesh, the pressing pressure is 100-150 MPa, the sintering temperature is 900-1100℃, and the holding time is 0.5-5h.

[0019] Furthermore, the coating in step 2 is carried out by spraying; the spraying uses a high-pressure gas source, and the gas is one of compressed air, N2, Ar, or CO2. During the spraying process, the gas pressure is 0.03 to 0.08 MPa and the gas flow rate is 20 to 40 L / min.

[0020] Furthermore, during the spraying process, the porous Ti support layer rotates at a constant speed, and the nozzle moves back and forth at a constant speed along the axial direction of the Ti tube; after the spraying is completed, drying is performed to obtain the final product.

[0021] Furthermore, in step 3, the drying process involves first air drying, followed by vacuum drying. The air drying time is 10–30 minutes, and the vacuum drying is carried out at 30–50°C for 20–40 minutes.

[0022] An asymmetric porous Ti tube, comprising an inner macroporous support layer and an outer microporous separation layer; wherein the macroporous support layer has a pore size of 5–100 μm and the microporous separation layer has a pore size of 0.1–10 μm.

[0023] An application of an asymmetric porous Ti tube, wherein the asymmetric porous Ti tube is used in the preparation of solid-liquid separation and gas-solid separation devices.

[0024] The beneficial effects of this invention are:

[0025] (1) The porous titanium tube obtained by the present invention includes an internal macroporous support layer and a microporous separation layer disposed on its outer wall. The porous asymmetric titanium tube has both high throughput and high filtration accuracy.

[0026] (2) The preparation method of the present invention is simple, the process is stable, the efficiency is high and the controllability is good; the obtained porous titanium tube has abundant pores.

[0027] (3) The porous titanium tube obtained by the present invention is easy to form a dense TiO2 film with stable physical and chemical properties inside and outside the tube and on the surface of the pores during storage and use, which can prevent the internal Ti from being corroded and has a long service life.

[0028] (4) When the asymmetric porous titanium tube of the present invention is used for filtration, the filter residue is on the outside of the separation layer and will not enter the macroporous matrix to block the pores. The filtration resistance increases slowly, the backflushing cleaning interval is long, and the filtration efficiency is high. Attached Figure Description

[0029] Figure 1This is a SEM image of the cross-section of the asymmetric porous Ti tube obtained in Embodiment 1 of the present invention.

[0030] Figure 2 This is a SEM image of the surface of the asymmetric porous Ti tube obtained in Embodiment 1 of the present invention. Detailed Implementation

[0031] The present invention will be further described below with reference to the accompanying drawings and specific embodiments.

[0032] A method for preparing an asymmetric porous Ti tube includes the following steps:

[0033] Step 1: Ball mill the TiH2 powder and the spacer separately to refine them. Add the ball-milled TiH2 powder and spacer to an appropriate amount of solvent used for the dispersant pretreatment solution, and disperse and mix them using ultrasonic-assisted stirring to obtain a mixed solution. Then add the dispersant pretreatment solution and continue ultrasonic-assisted stirring to disperse and mix, obtaining a uniform and stable slurry for later use.

[0034] Because fine powders are prone to agglomeration, ultrasonic-assisted stirring is required to disperse the agglomerated powders. The degree of dispersion of the spacer and TiH2 powder has a significant impact on the integrity and strength of the separation layer. If the spacer is not dispersed uniformly, it cannot effectively reduce the shrinkage of the separation layer, leading to cracks in the separation layer. In addition, because the dispersant pre-solution has a certain viscosity, the spacer and TiH2 powder are difficult to disperse directly in the dispersant pre-solution; therefore, they must be dispersed first using the pre-solution solvent.

[0035] The initial TiH2 powder particle size is 100–1000 mesh. The TiH2 powder ball milling process is as follows: ball-to-powder ratio of 3:1–5:1, ball milling time of 3–18 hours, and ethanol as the milling medium. TiH2 powder is brittle and easily broken; therefore, a smaller ball-to-powder ratio and shorter ball milling time are preferable to save time and energy and reduce the introduction of impurities. Simultaneously, a small amount of dehydrogenation occurs during TiH2 powder ball milling, which increases the pressure inside the milling jar. Therefore, a milling jar equipped with a valve for vacuuming and gas filling is recommended for timely pressure relief and reduction to ensure safety.

[0036] The site-forming agent is selected from substances that are stable during medium-temperature sintering, sinter at high temperatures, or are easily removed later, such as some high-melting-point salts and metal oxides. It is stable during medium-temperature sintering, promoting sintering between Ti powder particles through surface diffusion and maintaining the integrity of the coating. During high-temperature sintering, it either decomposes or is removed due to volatilization caused by the saturated vapor pressure being higher than that in a vacuum furnace, or it can be removed by washing with water or acid after exiting the furnace. If easily decomposed or volatile pore-forming agents are selected, premature loss of the pore-forming agent during medium-temperature sintering will still cause the film to shrink, eventually leading to defects such as cracks and damage. In this invention, K2SO4 is preferably used as the site-forming agent. K2SO4 has a high melting point (1067℃), is insoluble in ethanol, easily soluble in water, is not hygroscopic, and has stable chemical properties at high temperatures, making it difficult to decompose.

[0037] The ball milling process for the placer is as follows: the ball-to-material ratio is 3:1 to 6:1, the ball milling time is 20 to 60 hours, and the ball milling medium is ethanol.

[0038] The dispersant pretreatment solution is ethanol-polyvinyl butyral (PVB). Ethanol is volatile and has good dispersibility for agglomerated powders. After coating, the film layer can dry quickly, which is beneficial for film layer shaping and shortens the process time. Moreover, ethanol does not dissolve K2SO4. PVB leaves no residue after decomposition, and the decomposition temperature is basically the same as the dehydrogenation temperature of TiH2 powder. The two can be carried out simultaneously, shortening the sintering process.

[0039] The dispersant pre-prepared solution is prepared by mixing ethanol and PVB at a mass ratio of 1:0.5-2. After stirring until the solution is basically transparent, it is allowed to stand and sealed until the solution is completely transparent before it can be stored for later use. Since PVB powder takes a long time to dissolve in ethanol, it is not advisable to prepare it immediately before use. It can be prepared in advance and sealed for long-term use.

[0040] The mass ratio of K2SO4 to TiH2 powder in the mixed solution is 1:3.5-9, and the mass ratio of the slurry containing the dispersant pre-prepared solution, the total weight of K2SO4 and TiH2 after ball milling, and the ethanol for dispersion is 5-8:7-10:5-8.

[0041] Step 2: Coat the slurry obtained in Step 1 onto the surface of the porous Ti support layer to obtain a green body;

[0042] The Ti support layer is formed by pressing and sintering. Ti powder is loaded into a mold and cold isostatic pressing is performed. The particle size of the Ti powder is 500-100 mesh, the pressing pressure is 100-150 MPa, the sintering temperature is 900-1100℃, and the holding time is 0.5-5h.

[0043] The coating method employs spraying. Compressed air, N2, Ar, and CO2 are used as the spraying gases, with a pressure of 0.03–0.08 MPa and a flow rate of 20–40 L / min. During spraying, the Ti tube substrate is rotated at a uniform speed, and the nozzle moves back and forth along the axis of the Ti tube at a uniform speed, ensuring the slurry is evenly coated onto the surface of the Ti tube substrate. After a certain thickness of slurry is evenly applied to the surface, the slurry reaches a critical flow state due to insufficient drying time. At this point, spraying can be stopped, and auxiliary heating can be used for drying. Ethanol-based dispersants are easy to dry; after a brief drying period, spraying can continue, allowing for control of the coating thickness as needed.

[0044] Step 3: After drying the green blank obtained in Step 2, sinter it to obtain the desired asymmetric porous Ti tube.

[0045] The sintering process is gradient sintering, and the sintering regime is as follows:

[0046] Heat to 120–150℃ and hold for 20–40 minutes; dehydrate at this temperature.

[0047] When the temperature is below 300℃, the temperature is increased at a rate of ≤5℃ / min. When the temperature is above 300℃, the temperature is increased at a rate of less than 3℃ / min to 300-600℃, and the temperature is maintained at a gradient for 3-8 hours. Degreasing and dehydrogenation are carried out at this temperature. The heating rate is less than 5℃ / min to prevent the membrane from being damaged by severe degreasing and dehydrogenation.

[0048] Heat to 750–850℃ and hold for 1–5 hours;

[0049] The temperature is raised to 850–1000℃ and held for 0.5–2 hours. This sintering temperature is lower than the sintering temperature of the porous Ti tube support layer to prevent the Ti tube substrate from further sintering, shrinking, and deforming.

[0050] The sintering process consists of three stages: low-temperature dehydration, degreasing, and dehydrogenation; medium-temperature sintering; and high-temperature sintering. Low-temperature dehydration and degreasing remove residual moisture and organic dispersants from the sintering furnace and green body, allowing the film to solidify. Dehydrogenation produces highly active Ti powder particles in the coating layer, while the generated hydrogen further hydrogenates and dehydrogenates the Ti in the support layer, resulting in a highly active Ti surface in the support layer as well. This promotes sintering between the support and coating layers and enhances the interfacial bonding strength between the support and separation layers. Medium-temperature sintering ensures that the diffusion of dehydrogenated Ti powder between the coating layers primarily occurs through surface diffusion. When surface diffusion is the dominant mode of material migration, the interparticle spacing shrinks less, leading to less film shrinkage and reducing the shrinkage difference between the coating and support layers, preventing cracks and damage to the coating. High-temperature sintering further improves the coating strength.

[0051] Example 1

[0052] A method for preparing an asymmetric porous Ti tube includes the following steps:

[0053] Step 1: Prepare the slurry

[0054] First, TiH2 powder and K2SO4 were ball-milled separately using a planetary ball mill. The wet grinding medium was ethanol, and the rotation speed was 200 r / min.

[0055] The initial particle size of TiH2 powder was 200 mesh, the ball-to-material ratio was 4:1, and the ball milling time was 8 hours; the ball-to-material ratio of K2SO4 was 5:1, and the ball milling time was 48 hours.

[0056] Mix PVB powder and anhydrous ethanol at a mass ratio of 5:4, stir thoroughly until basically colorless and transparent, seal and let stand for 12 hours before use.

[0057] 0.45 parts of ball-milled K2SO4 powder were placed in 2 parts of anhydrous ethanol and stirred with ultrasonic assistance until the ball-milled K2SO4 powder was dispersed until there were no obvious particles. Then, 2.55 parts of ball-milled TiH2 powder were added and stirred with ultrasonic assistance until there were no obvious particles in the solution. Finally, 2 parts of PVB / ethanol pre-mixed solution were added and stirred to mix evenly to obtain the spraying slurry.

[0058] Step 2: Coat the slurry obtained in Step 1 onto the surface of the porous Ti support layer to obtain a green body.

[0059] First, a porous Ti support layer was prepared: 400-mesh Ti powder was selected, and the cold isostatic pressing pressure was 120 MPa; the sintering temperature was 900℃ for 2 hours.

[0060] Spray coating: High-pressure argon gas is used as the gas source, the spray gun pressure is 0.05MPa, the Ti tube is rotated at 10r / min, and the spray gun travel speed is 5cm / min.

[0061] After coating, keep the Ti tube rotating and air dry for 20 minutes. Remove the Ti tube and transfer it to a vacuum oven, where it is vacuum dried at 40°C for 30 minutes.

[0062] Step 3: After drying the green blank obtained in Step 2, sinter it to obtain the desired asymmetric porous Ti tube.

[0063] The dried sample is transferred to a sintering furnace and heated in stages to carry out dehydrogenation, degreasing, and sintering.

[0064] Specific sintering process:

[0065] Low-temperature sintering: Stage 1, heat from room temperature to 120℃ for 30 minutes and hold for 30 minutes;

[0066] Stage 2: 50 min to 300℃, hold for 30 min; 15 min to 350℃, hold for 30 min; 15 min to 400℃, hold for 1.5 h; 20 min to 450℃, hold for 1 h; 40 min to 550℃, hold for 1 h; 15 min to 600℃, hold for 30 min; Stage 2 consists of 6 steps for sintering.

[0067] Medium-temperature sintering: Heat to 800℃ for 40 minutes and hold for 2 hours;

[0068] High-temperature sintering: Heat to 880℃ in 30 minutes and hold for 2 hours; then cool with the furnace.

[0069] Figure 1 This is a cross-sectional SEM image of the asymmetric porous Ti tube obtained in Example 1. Figure 2 The image shows a SEM image of the surface. It can be seen from the image that the obtained porous Ti tube cross-section has an asymmetric porous structure with pore sizes ranging from 1.0 to 2.4 μm.

[0070] The asymmetric porous Ti tube obtained in this embodiment has a pure water flux of 2180-2300 L / h (0.06 MPa) and a filtration accuracy of 0.1 μm. The asymmetric porous Ti tube shows no obvious deformation, and no obvious cracks or damage are found in the separation layer at the macroscopic or microscopic level.

[0071] Example 2

[0072] A method for preparing an asymmetric porous Ti tube includes the following steps:

[0073] Step 1: Prepare the slurry

[0074] First, TiH2 powder and K2SO4 were ball-milled separately using a planetary ball mill. The wet grinding medium was ethanol, and the rotation speed was 200 r / min.

[0075] The initial particle size of TiH2 powder was 400 mesh, the ball-to-material ratio was 3:1, and the ball milling time was 18h; the ball-to-material ratio of K2SO4 was 3:1, and the ball milling time was 60h.

[0076] Mix PVB powder and anhydrous ethanol at a mass ratio of 0.5:1, stir thoroughly until basically colorless and transparent, seal and let stand for 12 hours before use.

[0077] 0.45 parts of ball-milled K2SO4 powder were placed in 3 parts of anhydrous ethanol and stirred with ultrasonic assistance until the ball-milled K2SO4 powder was dispersed until there were no obvious particles. Then, 2.55 parts of ball-milled TiH2 powder were added and stirred with ultrasonic assistance until there were no obvious particles in the solution. Finally, 3 parts of PVB / ethanol pre-mixed solution were added and stirred evenly to obtain the spraying slurry.

[0078] Step 2: Coat the slurry obtained in Step 1 onto the surface of the porous Ti support layer to obtain a green body.

[0079] First, a porous Ti support layer was prepared: 100-mesh Ti powder was selected, and the cold isostatic pressing pressure was 120 MPa; the sintering temperature was 1100℃ for 2 hours.

[0080] Spray coating: High-pressure argon gas is used as the gas source, the spray gun pressure is 0.03MPa, the Ti tube is rotated at 10r / min, and the spray gun travel speed is 5cm / min.

[0081] After coating, keep the Ti tube rotating and air dry for 30 minutes. Remove the Ti tube and transfer it to a vacuum oven, where it is vacuum dried at 50°C for 20 minutes.

[0082] Step 3: After drying the green blank obtained in Step 2, sinter it to obtain the desired asymmetric porous Ti tube.

[0083] The dried sample is transferred to a sintering furnace and heated in stages to carry out dehydrogenation, degreasing, and sintering.

[0084] Specific sintering process:

[0085] Low-temperature sintering: Stage 1, heat from room temperature to 120℃ for 30 minutes and hold for 30 minutes;

[0086] Stage 2: 50 min to 300℃, hold for 30 min; 15 min to 350℃, hold for 30 min; 15 min to 400℃, hold for 1.5 h; 20 min to 450℃, hold for 1 h; 40 min to 550℃, hold for 1 h; 15 min to 600℃, hold for 30 min; Stage 2 consists of 6 steps for sintering.

[0087] Medium-temperature sintering: Heat to 800℃ for 40 minutes and hold for 2 hours;

[0088] High-temperature sintering: Heat to 880℃ in 30 minutes and hold for 2 hours; then cool with the furnace.

[0089] After sintering, the asymmetric porous Ti tubes exhibit a pure water flux of 2190–2320 L / h (0.06 MPa), a pore size of 1.1–2.3 μm, and a filtration accuracy of 0.1 μm. The asymmetric porous Ti tubes show no significant deformation, and no obvious cracks or damage are observed in the separation layer at either the macroscopic or microscopic level. The strength between the support layer and the separation layer is high. (Higher flux with minimal change in filtration accuracy)

[0090] Example 3

[0091] A method for preparing an asymmetric porous Ti tube includes the following steps:

[0092] Step 1: Prepare the slurry

[0093] First, TiH2 powder and K2SO4 were ball-milled separately using a planetary ball mill. The wet grinding medium was ethanol, and the rotation speed was 200 r / min.

[0094] The initial particle size of TiH2 powder was 200 mesh, the ball-to-material ratio was 5:1, and the ball milling time was 3 hours; the ball-to-material ratio of K2SO4 was 6:1, and the ball milling time was 20 hours.

[0095] Mix PVB powder and anhydrous ethanol at a mass ratio of 2:1, stir thoroughly until basically colorless and transparent, seal and let stand for 12 hours before use.

[0096] 0.45 parts of ball-milled K2SO4 powder were placed in 2.2 parts of anhydrous ethanol and stirred with ultrasonic assistance until the ball-milled K2SO4 powder was dispersed until there were no obvious particles. Then, 2.55 parts of ball-milled TiH2 powder were added and stirred with ultrasonic assistance until there were no obvious particles in the solution. Finally, 2 parts of PVB / ethanol pre-mixed solution were added and stirred evenly to obtain the spraying slurry.

[0097] Step 2: Coat the slurry obtained in Step 1 onto the surface of the porous Ti support layer to obtain a green body.

[0098] First, a porous Ti support layer was prepared: 500-mesh Ti powder was selected, and the cold isostatic pressing pressure was 120 MPa; the sintering temperature was 900℃ for 2 hours.

[0099] Spray coating: High-pressure argon gas is used as the gas source, the spray gun pressure is 0.04MPa, the Ti tube is rotated at 10r / min, and the spray gun travel speed is 5cm / min.

[0100] After coating, keep the Ti tube rotating and air dry for 10 minutes. Remove the Ti tube and transfer it to a vacuum oven, where it is vacuum dried at 30°C for 40 minutes.

[0101] Step 3: After drying the green blank obtained in Step 2, sinter it to obtain the desired asymmetric porous Ti tube.

[0102] The dried sample is transferred to a sintering furnace and heated in stages to carry out dehydrogenation, degreasing, and sintering.

[0103] Specific sintering process:

[0104] Low-temperature sintering: Stage 1, heat from room temperature to 120℃ for 30 minutes and hold for 30 minutes;

[0105] Stage 2: 50 min to 300℃, hold for 30 min; 15 min to 350℃, hold for 30 min; 15 min to 400℃, hold for 1.5 h; 20 min to 450℃, hold for 1 h; 40 min to 550℃, hold for 1 h; 15 min to 600℃, hold for 30 min; Stage 2 consists of 6 steps for sintering.

[0106] Medium-temperature sintering: Heat to 800℃ for 40 minutes and hold for 4 hours;

[0107] High-temperature sintering: Heat to 880℃ in 30 minutes and hold for 1.5 hours; then cool with the furnace.

[0108] The sintered asymmetric porous Ti tubes exhibit a pure water flux of 2260–2520 L / h (0.06 MPa), a pore size of 1.8–3.1 μm, and a filtration accuracy of 0.15 μm. The asymmetric porous Ti tubes show no significant deformation, and no obvious cracks or damage are observed in the separation layer at either the macroscopic or microscopic level. The strength between the support layer and the separation layer is high. (Compared to Example 1, the flux is higher, but the filtration accuracy is slightly lower.)

[0109] Example 4

[0110] A method for preparing an asymmetric porous Ti tube includes the following steps:

[0111] Step 1: Prepare the slurry

[0112] First, TiH2 powder and K2SO4 were ball-milled separately using a planetary ball mill. The wet grinding medium was ethanol, and the rotation speed was 200 r / min.

[0113] The initial particle size of TiH2 powder was 200 mesh, the ball-to-material ratio was 4:1, and the ball milling time was 10 hours; the ball-to-material ratio of K2SO4 was 5:1, and the ball milling time was 24 hours.

[0114] Mix PVB powder and anhydrous ethanol at a mass ratio of 5:6, stir thoroughly until basically colorless and transparent, seal and let stand for 12 hours before use.

[0115] 0.45 parts of ball-milled K2SO4 powder were placed in 1.8 parts of anhydrous ethanol and stirred with ultrasonic assistance until the ball-milled K2SO4 powder was dispersed until there were no obvious particles. Then, 2.55 parts of ball-milled TiH2 powder were added and stirred with ultrasonic assistance until there were no obvious particles in the solution. Finally, 2.1 parts of PVB / ethanol pre-mixed solution were added and stirred until the mixture was homogeneous to obtain the spraying slurry.

[0116] Step 2: Coat the slurry obtained in Step 1 onto the surface of the porous Ti support layer to obtain a green body.

[0117] First, a porous Ti support layer was prepared: 100-mesh Ti powder was selected, and the cold isostatic pressing pressure was 120 MPa; the sintering temperature was 1050℃ for 2 hours.

[0118] Spray coating: High-pressure argon gas is used as the gas source, the spray gun pressure is 0.05MPa, the Ti tube is rotated at 10r / min, and the spray gun travel speed is 5cm / min.

[0119] After coating, keep the Ti tube rotating and air dry for 10 minutes. Remove the Ti tube and transfer it to a vacuum oven, where it is vacuum dried at 40°C for 30 minutes.

[0120] Step 3: After drying the green blank obtained in Step 2, sinter it to obtain the desired asymmetric porous Ti tube.

[0121] The dried sample is transferred to a sintering furnace and heated in stages to carry out dehydrogenation, degreasing, and sintering.

[0122] Specific sintering process:

[0123] Low-temperature sintering: Stage 1, heat from room temperature to 120℃ for 30 minutes and hold for 30 minutes;

[0124] Stage 2: 50 min to 300℃, hold for 30 min; 15 min to 350℃, hold for 30 min; 15 min to 400℃, hold for 1.5 h; 20 min to 450℃, hold for 1 h; 40 min to 550℃, hold for 1 h; 15 min to 600℃, hold for 30 min; Stage 2 consists of 6 steps for sintering.

[0125] Medium-temperature sintering: Heat to 800℃ for 40 minutes and hold for 5 hours;

[0126] High-temperature sintering: Heat to 880℃ in 30 minutes and hold for 1 hour; then cool with the furnace.

[0127] The sintered asymmetric porous Ti tubes exhibit a pure water flux of 2090–2150 L / h (0.06 MPa), a pore size of 0.9–1.5 μm, and a filtration accuracy of 0.1 μm. The asymmetric porous Ti tubes show no significant deformation, and no obvious cracks or damage are observed in the separation layer at either the macroscopic or microscopic level. The strength between the support layer and the separation layer is high. (Compared to Example 1, the flux is greater, and the filtration accuracy is slightly increased.)

[0128] Example 5

[0129] A method for preparing an asymmetric porous Ti tube includes the following steps:

[0130] Step 1: Prepare the slurry

[0131] First, TiH2 powder and K2SO4 were ball-milled separately using a planetary ball mill. The wet grinding medium was ethanol, and the rotation speed was 200 r / min.

[0132] The initial particle size of TiH2 powder was 200 mesh, the ball-to-material ratio was 4:1, and the ball milling time was 10 hours; the ball-to-material ratio of K2SO4 was 5:1, and the ball milling time was 24 hours.

[0133] Mix PVB powder and anhydrous ethanol at a mass ratio of 5:6, stir thoroughly until basically colorless and transparent, seal and let stand for 12 hours before use.

[0134] 0.45 parts of ball-milled K2SO4 powder were placed in 1.8 parts of anhydrous ethanol and stirred with ultrasonic assistance until the ball-milled K2SO4 powder was dispersed until there were no obvious particles. Then, 2.55 parts of ball-milled TiH2 powder were added and stirred with ultrasonic assistance until there were no obvious particles in the solution. Finally, 2.1 parts of PVB / ethanol pre-mixed solution were added and stirred until the mixture was homogeneous to obtain the spraying slurry.

[0135] Step 2: Coat the slurry obtained in Step 1 onto the surface of the porous Ti support layer to obtain a green body.

[0136] First, a porous Ti support layer was prepared: 100-mesh Ti powder was selected, and the cold isostatic pressing pressure was 120 MPa; the sintering temperature was 1050℃ for 2 hours.

[0137] Spray coating: High-pressure argon gas is used as the gas source, the spray gun pressure is 0.05MPa, the Ti tube is rotated at 10r / min, and the spray gun travel speed is 5cm / min.

[0138] After coating, keep the Ti tube rotating and air dry for 10 minutes. Remove the Ti tube and transfer it to a vacuum oven, where it is vacuum dried at 40°C for 30 minutes.

[0139] Step 3: After drying the green blank obtained in Step 2, sinter it to obtain the desired asymmetric porous Ti tube.

[0140] The dried sample is transferred to a sintering furnace and heated in stages to carry out dehydrogenation, degreasing, and sintering.

[0141] Specific sintering process:

[0142] Low-temperature sintering: Stage 1, heat up from room temperature for 40 minutes to 150℃, and hold for 20 minutes;

[0143] Phase 2: Increase the temperature to 300℃ in 40 minutes and hold for 10 minutes; increase the temperature to 400℃ in 1 hour and hold for 3 hours; increase the temperature to 500℃ in 1 hour and hold for 4 hours.

[0144] Medium-temperature sintering: Heat to 850℃ for 40 minutes and hold for 1 hour;

[0145] High-temperature sintering: Heat to 1000℃ in 30 minutes and hold for 0.5 hours; then cool with the furnace.

[0146] Example 6

[0147] A method for preparing an asymmetric porous Ti tube includes the following steps:

[0148] Step 1: Prepare the slurry

[0149] First, TiH2 powder and K2SO4 were ball-milled separately using a planetary ball mill. The wet grinding medium was ethanol, and the rotation speed was 200 r / min.

[0150] The initial particle size of TiH2 powder was 200 mesh, the ball-to-material ratio was 4:1, and the ball milling time was 10 hours; the ball-to-material ratio of K2SO4 was 5:1, and the ball milling time was 24 hours.

[0151] Mix PVB powder and anhydrous ethanol at a mass ratio of 5:6, stir thoroughly until basically colorless and transparent, seal and let stand for 12 hours before use.

[0152] 0.45 parts of ball-milled K2SO4 powder were placed in 1.8 parts of anhydrous ethanol and stirred with ultrasonic assistance until the ball-milled K2SO4 powder was dispersed until there were no obvious particles. Then, 2.55 parts of ball-milled TiH2 powder were added and stirred with ultrasonic assistance until there were no obvious particles in the solution. Finally, 2.1 parts of PVB / ethanol pre-mixed solution were added and stirred until the mixture was homogeneous to obtain the spraying slurry.

[0153] Step 2: Coat the slurry obtained in Step 1 onto the surface of the porous Ti support layer to obtain a green body.

[0154] First, a porous Ti support layer was prepared: 100-mesh Ti powder was selected, and the cold isostatic pressing pressure was 120 MPa; the sintering temperature was 1050℃ for 2 hours.

[0155] Spray coating: High-pressure argon gas is used as the gas source, the spray gun pressure is 0.05MPa, the Ti tube is rotated at 10r / min, and the spray gun travel speed is 5cm / min.

[0156] After coating, keep the Ti tube rotating and air dry for 10 minutes. Remove the Ti tube and transfer it to a vacuum oven, where it is vacuum dried at 40°C for 30 minutes.

[0157] Step 3: After drying the green blank obtained in Step 2, sinter it to obtain the desired asymmetric porous Ti tube.

[0158] The dried sample is transferred to a sintering furnace and heated in stages to carry out dehydrogenation, degreasing, and sintering.

[0159] Specific sintering process:

[0160] Low-temperature sintering: Stage 1, heat from room temperature to 120℃ for 40 minutes and hold for 40 minutes;

[0161] Phase 2: Increase the temperature to 300℃ in 40 minutes and hold for 10 minutes; increase the temperature to 450℃ in 3 hours and hold for 2 hours; increase the temperature to 600℃ in 1 hour and hold for 1 hour.

[0162] Medium-temperature sintering: Heat to 750℃ for 40 minutes and hold for 5 hours;

[0163] High-temperature sintering: Heat to 850℃ in 30 minutes and hold for 2 hours; then cool with the furnace.

[0164] Example 7

[0165] A method for preparing an asymmetric porous Ti tube includes the following steps:

[0166] Step 1: Prepare the slurry

[0167] First, TiH2 powder and K2SO4 were ball-milled separately using a planetary ball mill. The wet grinding medium was ethanol, and the rotation speed was 200 r / min.

[0168] The initial particle size of TiH2 powder was 200 mesh, the ball-to-material ratio was 4:1, and the ball milling time was 10 hours; the ball-to-material ratio of K2SO4 was 5:1, and the ball milling time was 24 hours.

[0169] Mix PVB powder and anhydrous ethanol at a mass ratio of 5:6, stir thoroughly until basically colorless and transparent, seal and let stand for 12 hours before use.

[0170] 0.45 parts of ball-milled K2SO4 powder were placed in 1.8 parts of anhydrous ethanol and stirred with ultrasonic assistance until the ball-milled K2SO4 powder was dispersed until there were no obvious particles. Then, 2.55 parts of ball-milled TiH2 powder were added and stirred with ultrasonic assistance until there were no obvious particles in the solution. Finally, 2.1 parts of PVB / ethanol pre-mixed solution were added and stirred until the mixture was homogeneous to obtain the spraying slurry.

[0171] Step 2: Coat the slurry obtained in Step 1 onto the surface of the porous Ti support layer to obtain a green body.

[0172] First, a porous Ti support layer was prepared: 100-mesh Ti powder was selected, and the cold isostatic pressing pressure was 120 MPa; the sintering temperature was 1050℃ for 2 hours.

[0173] Spray coating: High-pressure argon gas is used as the gas source, the spray gun pressure is 0.05MPa, the Ti tube is rotated at 10r / min, and the spray gun travel speed is 5cm / min.

[0174] After coating, keep the Ti tube rotating and air dry for 10 minutes. Remove the Ti tube and transfer it to a vacuum oven, where it is vacuum dried at 40°C for 30 minutes.

[0175] Step 3: After drying the green blank obtained in Step 2, sinter it to obtain the desired asymmetric porous Ti tube.

[0176] The dried sample is transferred to a sintering furnace and heated in stages to carry out dehydrogenation, degreasing, and sintering.

[0177] Specific sintering process:

[0178] Low-temperature sintering: Stage 1, heat up from room temperature for 40 minutes to 150℃, and hold for 20 minutes;

[0179] Phase 2: Increase the temperature to 300℃ in 50 minutes and hold for 2 hours; then increase the temperature to 500℃ in 4 hours and hold for 3 hours.

[0180] Medium-temperature sintering: Heat to 850℃ for 40 minutes and hold for 1 hour;

[0181] High-temperature sintering: Heat to 1000℃ in 30 minutes and hold for 0.5 hours; then cool with the furnace.

[0182] To make a comparison, a scale is set up. The comparison process is as follows:

[0183] Comparative Example 1

[0184] The other preparation processes are the same as in Example 1, except that the dispersant is changed from a PVB and anhydrous ethanol system to a 10 wt.% PVA aqueous solution.

[0185] The obtained asymmetric porous Ti tubes showed no obvious deformation, but the separation layer had low strength, severe powder shedding, and poor bonding between the separation layer and the support layer.

[0186] Comparative Example 2

[0187] The other preparation processes are the same as in Example 1, except that the Ti source for coating is replaced with Ti powder instead of TiH2 powder.

[0188] The obtained asymmetric porous Ti tubes showed no obvious deformation, but the separation layer showed obvious cracks and damage on both the macroscopic and microscopic levels. The support layer and the separation layer were poorly bonded and prone to peeling and powdering.

[0189] Comparative Example 3

[0190] The other preparation processes are the same as in Example 1, except that the temperature is 950℃ for 2 hours during the high-temperature sintering stage after coating.

[0191] After sintering, the pure water flux of the asymmetric porous Ti tube was 1890–2020 L / h (0.06 MPa), and the pore size was 0.5–0.9 μm. The separation layer of the asymmetric porous Ti tube showed obvious cracks and damage at both the macroscopic and microscopic levels, and the Ti tube as a whole shrank and deformed. (Compared to Example 1, the flux was extremely low.)

[0192] This invention designs a porous titanium tube as a macroporous support layer and a microporous separation layer, enabling the asymmetric Ti tube to achieve both high throughput and high filtration accuracy. By adding a placebo to the separation layer, shrinkage is reduced, preventing cracks and damage to the asymmetric porous Ti membrane due to sintering shrinkage. TiH2 powder is selected as the coating material, ensuring high bonding strength between the macroporous support layer and the microporous separation layer. The sintering process is controlled to ensure that atomic diffusion during coating sintering is primarily surface diffusion, reducing coating shrinkage and preventing cracks and damage. The appropriate viscosity of the coating slurry is controlled to prevent fine powder from entering the macroporous support layer and reducing throughput. The filtered liquid enters from the microporous separation layer side and exits from the macroporous support layer, reducing the amount of filtered material entering the support layer and maintaining the membrane's low-resistivity characteristics.

Claims

1. A method for preparing an asymmetric porous Ti tube, characterized in that, Includes the following steps: Step 1: Ball mill the TiH2 powder and the spacer separately; disperse the ball-milled TiH2 powder and spacer in a solvent and mix to obtain a mixed solution; add the mixed solution to the dispersant pre-prepared liquid and mix thoroughly to obtain a slurry; wherein the mass ratio of TiH2 powder to spacer in the slurry is 3.5–9:1; the spacer is K2SO4; the dispersant pre-prepared liquid in Step 1 is composed of polyvinyl butyral and solvent mixed at a mass ratio of 0.5–2:1; wherein the mass ratio of the total amount of dispersant pre-prepared liquid, spacer, and TiH2 powder to the solvent in the slurry is 5–8:7–10:5–8; the particle size of the TiH2 powder is 500–100 mesh, and the ball milling process of the TiH2 powder is as follows: ball-to-powder ratio is 3–5:1, and the ball milling time is 3–18 h; the ball milling process of the spacer is as follows: ball-to-powder ratio is 3–6:1, and the ball milling time is 20–60 h; Step 2: Coat the slurry obtained in Step 1 onto the surface of the porous Ti support layer to obtain a green body; Step 3: After drying the green body obtained in Step 2, sinter it to obtain the desired asymmetric porous Ti tube; the sintering is gradient sintering, and the sintering regime is as follows: Low-temperature sintering: Stage 1: Heat to 120–150 °C and hold for 20–40 min; In stage 2, when the temperature is below 300℃, the temperature is increased at a rate of ≤5℃ / min; when the temperature is above 300℃, the temperature is increased at a rate of less than 3℃ / min to the range of 300 to 600℃, and then the temperature is maintained at a gradient for 3 to 8 hours. Medium-temperature sintering: Heat to 750–850 ℃ and hold for 1–5 h; High-temperature sintering: Heat to 850–1000 ℃ and hold for 0.5–2 h; The asymmetric porous Ti tube includes a large-pore support layer in the inner layer and a fine-pore separation layer in the outer layer; wherein the pore diameter of the large-pore support layer is 5~100 µm and the pore diameter of the fine-pore separation layer is 0.1~10 μm.

2. The method for preparing an asymmetric porous Ti tube according to claim 1, characterized in that, Stage 2 of the sintering process is gradient sintering, which is divided into at least two steps.

3. The method for preparing an asymmetric porous Ti tube according to claim 1, characterized in that, The porous Ti support layer in step 2 is formed by pressing and sintering Ti powder. The particle size of the Ti powder is 500~100 mesh, the pressing pressure is 100~150MPa, the sintering temperature is 900~1100 ℃, and the holding time is 0.5~5 h.

4. The method for preparing an asymmetric porous Ti tube according to claim 1, characterized in that, The coating in step 2 is done by spraying. The spraying uses a high-pressure gas source, and the gas is one of compressed air, N2, Ar, or CO2. During the spraying process, the gas pressure is 0.03 to 0.08 MPa and the gas flow rate is 20 to 40 L / min.

5. The method for preparing an asymmetric porous Ti tube according to claim 4, characterized in that, During the spraying process, the porous Ti support layer rotates at a constant speed, and the nozzle moves back and forth at a constant speed along the axis of the Ti tube; after the spraying is completed, it is dried to obtain the final product.

6. The method for preparing an asymmetric porous Ti tube according to claim 1, characterized in that, In step 3, the drying process first involves air drying, followed by vacuum drying. The air drying time is 10–30 min, and the vacuum drying is carried out at 30–50 °C for 20–40 min.

7. The application of the asymmetric porous Ti tube obtained by the preparation method according to any one of claims 1 to 6, characterized in that, The asymmetric porous Ti tube is used in the preparation of solid-liquid separation and gas-solid separation devices.

Citation Information

Patent Citations

  • Method for preparing porous titanium coating on surface of titanium alloy

    CN103266319A